Enhancing Students’ Mathematical Creative Thinking through Problem-Based Learning: A Systematic Literature Review (2020–2025) - Liani, Ahyani Mirah; Asmaun (Cita konsultindo, 2025)
This study presents a systematic literature review of research published between 2020 and 2025 examining the effectiveness of Problem-Based Learning (PBL) in enhancing students’ mathematical creative thinking. The review synthesizes findings from peer-reviewed journal articles that investigated PBL within various educational contexts, including its integration with STEM frameworks, digital learning platforms, and the Indonesian Merdeka Curriculum. Data were collected through document analysis and literature tracing, followed by thematic synthesis to identify convergent findings across studies. The analysis reveals that PBL significantly improves key indicators of mathematical creative thinking—fluency, flexibility, originality, and elaboration—by engaging students in authentic, inquiry-driven problem-solving processes. Studies integrating PBL with digital tools such as GeoGebra and Google Classroom reported additional gains in originality and elaboration, demonstrating the benefits of technologically enriched, student-centered learning environments. STEM-based PBL further supported conceptual exploration and interdisciplinary reasoning. Beyond cognitive outcomes, the reviewed literature highlights improvements in students’ motivation, collaboration, and self-efficacy, which serve as affective foundations for creativity. Overall, the findings position PBL as a transformative pedagogical model aligned with 21st-century learning demands, offering strong potential for fostering creative, autonomous, and critical mathematical thinkers. Future research is recommended to explore long-term impacts and AI-supported PBL innovations.